Effect of oral infections on serum creatinine levels in diabetic rats - Cintra, Luciano Tavares Angelo [UNESP]; Facundo, Aguinaldo Cândido da Silva [UNESP]; Valentim, Diego [UNESP]; Prieto, Annelise Katrine Carrara [UNESP]; Silva, Cléverson Oliveira e; Sumida, Doris Hissako [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Dezan Junior, Eloi [UNESP]; Gomes Filho, João Eduardo [UNESP] (My University, 2013)
Aim: The aim of this study was to evaluate the relationship between pulpal and/or periodontal disease and serum creatinine levels in a rat model of diabetes mellitus. Methods: Eighty male rats (Rattus norvegicus albinus, Wistar) were divided into the following 8 groups compris-ing 10 animals each: normal (G1), with pulpal disease (G2), with periodontal disease (G3), with both pulpal and periodontal disease (G4), diabetic (G5), diabetic with pulpal disease (G6), diabetic with periodontal disease (G7), and diabetic with both pulpal and periodontal disease (G8). Diabetes was induced by injecting streptozotocin, pul-pal disease were induced by exposing pulpal tissue to the oral environment, and periodontal disease was induced by periodontal ligature. After 30 days, blood was collected by cardiac puncture and the animals were killed. The maxillae were processed for histopathology. Serum creatinine levels were measured by the enzymatic method. The total assessed values were statistically analyzed by analysis of variance and Tukey’s test (p < 0.05). Results: Serum creatinine levels were significantly higher in diabetic rats than that in all normoglycemic rats (p < 0.05). The presence of pulpal and periodontal disease increased the serum creatinine levels in normoglycemic and diabetic rats, but there was no statistical difference between the groups (p > 0.05). Conclusions: We found that the serum creatinine level was higher in diabetic rats and may be related to the pres-ence of oral infections. Clinical significance: Changes in serum creatinine level may be related to the presence of oral infections and diabetes.
Keywords: Diabetes; Apical periodontitis; Periodontal disease; Creatinine level